Management of Teaching Factory (TEFA) for Achieving Vocational School Graduate Competencies - Ade Tutty Rokhayati Rossa; Danang Ari Wibowo; Finsa Muhamad Pratama; Anita Fitri Rahmawati (Journal of Educational Management Research, 2025)
This study aims to analyse the implementation of Teaching Factory (TEFA) management to achieve graduate competencies at vocational schools. Teaching Factory (TEFA) is a production and service-based learning model that integrates school learning with the needs of the industrial world. This approach aims to produce graduates who are competent, work-ready, and possess skills according to industry standards. The results of this study indicate that the implementation of TEFA management at schools, encompassing planning, organising, implementation, evaluation, and follow-up, has been carried out effectively. The research used a descriptive method with a qualitative approach, involving observation, interviews, and documentation. The findings reveal that TEFA management implementation in schools includes planning based on industry needs, integrating learning with real-world projects, and evaluating outcomes based on work performance. Supporting factors for TEFA's success include close cooperation between schools and industries, the availability of supporting facilities, competent teachers, and effective follow-up management. However, this study also identified several obstacles, including limited facilities, a lack of continuous teacher training, and challenges in meeting the evolving needs of industry. Through optimal management, the Teaching Factory is expected to enhance the competitiveness of graduates and address labour market needs.